Competitive Education Marketing Management In Islamic Perspective - Ahmad Rifai; M. Lutfi Mustofa (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2026)
This study aims to find out the competitive management of education marketing from an Islamic perspective. This study uses a descriptive qualitative method. Data collection is carried out by observation and also a literature approach studio using literature sources related to the research problem. The results of the study show that competition between educational institutions is increasingly competitive; the importance of marketing strategies in introducing the advantages of the school to potential consumers or students; Islamic Perspective in the Phenomenon of Competition between Educational Institutions in Implementing Educational Management Strategies. The marketing strategy will usher in the school as a major educational institution as expected. Marketing strategy is the activity of finding ways to achieve a favorable exchange rate with customers that make customers the target to achieve the goals of the institution Keywords: Management; Educational Marketing, Islamic Perspective